Volcanic Eruptions in the Deep Sea - Kenneth H. Rubin; S. Adam Soule; William W. Chadwick Jr.; Daniel J. Fornari; David A. Clague; Robert W. Embley; Edward T. Baker; Michael R. Perfit; David W. Caress; Robert P. Dziak (Oceanography, 2012)
Volcanic eruptions are important events in Earth's cycle of magma generation and crustal construction. Over durations of hours to years, eruptions produce new deposits of lava and/or fragmentary ejecta, transfer heat and magmatic volatiles from Earth's interior to the overlying air or seawater, and significantly modify the landscape and perturb local ecosystems. Today and through most of geological history, the greatest number and volume of volcanic eruptions on Earth have occurred in the deep ocean along mid-ocean ridges, near subduction zones, on oceanic plateaus, and on thousands of mid-plate seamounts. However, deep-sea eruptions (> 500 m depth) are much more difficult to detect and observe than subaerial eruptions, so comparatively little is known about them. Great strides have been made in eruption detection, response speed, and observational detail since the first recognition of a deep submarine eruption at a mid-ocean ridge 25 years ago. Studies of ongoing or recent deep submarine eruptions reveal information about their sizes, durations, frequencies, styles, and environmental impacts. Ultimately, magma formation and accumulation in the upper mantle and crust, plus local tectonic stress fields, dictate when, where, and how often submarine eruptions occur, whereas eruption depth, magma composition, conditions of volatile segregation, and tectonic setting determine submarine eruption style.